The Speech Performance Observation Scale for Youth (SPOSY): Assessing Social Performance Characteristics Related to Social Anxiety. Issue 2 (July 2015) - Blöte, Anke W.; Poungjit, Apiradee; Miers, Anne C.; Van Beek, Yolanda; Westenberg, P. Michiel
This study describes the development of the SPOSY, an observation scale for speech performance of socially anxious youth. The scale was designed as a research tool to address specific behaviors that are readily noticed by non-expert others and might explain why socially anxious youth are rejected by peers. In Phase 1 of the study, items for the scale were generated based on "free" observations by naive observers. In Phase 2, the psychometric properties of the scale were evaluated using a sample of 218 speakers aged between 9 and 16 years. PCA with oblimin rotation yielded three reliable and stable factors, Expressiveness, Lack of confidence, and Agitation. Expressiveness was negatively related to Lack of confidence. Importantly, socially anxious youth were rated as less expressive and confident but not as more agitated in their behavior as compared to non- socially anxious youth. Low expressiveness seems related to safety behaviors and may play a significant role in peer rejection.